Coordinated optimal allocation of water resources and industrial structure in the Beijing–Tianjin–Hebei regions of China - Dan Wu; Mengyao Liu (Chinese Journal of Population, Resources and Environment, 2022)
ABSTRACT: Optimizing the allocation of water resources is critical for promoting the optimization and upgrading of industrial structure and coordinated development in the Beijing–Tianjin–Hebei regions of China. Based on specific regional and water conditions, to strengthen the constraints on water resources, the “three-step” adaptive management approach of “scheme design–scheme diagnosis–scheme optimization” of water resource allocation are adopted to facilitate the coordinated optimal allocation of water resources and industrial structure in the Beijing–Tianjin–Hebei regions. First, from the level of overall industry, a water resource allocation scheme for the regions is designed by applying the master–slave hierarchical mode and a bi-level optimal model to determine the ideal amount of water resource allocation for the regions and respective industries. Second, the diagnostic criteria of spatial balance, structural matching, and coordinated development are constructed to determine the rationality of the water resource allocation scheme. Then a benefit compensation function with water market transactions is developed, to adaptively adjust the water resource allocation scheme. Finally, the optimization and upgrading of industrial structure are promoted to improve water consumption efficiency and the coordinated development of the Beijing–Tianjin–Hebei regions. The study can provide reference for the Beijing–Tianjin–Hebei regions to realize the comprehensive optimal allocation of water resources in the regions and improve the adaptability of water resources and industrial structure optimization.